Influence of Wheat Flour Milling Yield on Physicochemical, Microbial, and Antioxidant Properties of Korea Wheat (Triticum aestivum L. var. Jokyoung) - Sang Sook Kim; Yang Soo Byeon; Mi Jeong Kim; Dabeen Lee; Han Sub Kwak (Journal of Food Quality)
The physicochemical, microbial, and antioxidant properties of a Korean wheat variety (Jokyoung) were measured according to milling yield (60–90%) by adding fractions from millstreams. As the milling yield increased, the wheat flour showed low quality on physicochemical properties in general. Significant differences in proximate analysis, color, solvent retention capacity, pasting property, and antioxidant activity were observed as the yield increased to maximize the production of wheat flour from wheat kernels. Adding clear flour and shorts did not significantly affect the quality of the wheat flour in comparison with straight flour samples. However, as brans were added to the flour portion, the wheat flour quality parameters decreased significantly in color, solvent retention capacity, and pasting properties. On the other hand, antioxidant properties increased as brans were added. Maximizing wheat flour yield is a key to minimizing the production cost of Korean wheat flour, which is approximately three times more expensive than imported wheat flour. Adding clear flour and a certain portion of shorts did not seem to significantly influence the overall quality of wheat flour from Korean domestic wheat variety.